Classification and Syntaxonomic Analysis of Plant Communities in the Yenice Wildlife Conservation Area, Northwestern Türkiye - Öztürk Pulatoğlu, Ayşe; Güney, Kerim (Kastamonu University, 2025)
Aim of study: The aim of the study is to reveal the vegetation structure of the study area, which is a conservation area. Area of study: The study area is the Yenice Wildlife Conservation Area in Karabük which is located in the western Black Sea region in Türkiye. Material and method: In order to determine the relationship of the plants in the area with their environment, 120 relevés were determined by taking into account the habitat, vegetation and floristic composition from different vegetation types. The tables were evaluated by using the "Braun-Blanquet method" in the interpretation of the vegetation of the study area. In addition, the JUICE 7.0 program was used to determine the diagnostic, constant and dominant species objectively. The naming of the determined sociological units was made according to the “International Code of Phytosociological Nomenclature”. Main results: The dominant vegetation type of the study area which includes many ecosystems such as forest, pseudomaquis, and riparian ecosystem due to its biogeographic location, is forest formation. According to the Braun-Blanquet method, 4 plant associations belonging to forest vegetation were determined. Research highlights: Corno mas-Quercetum ibericae ass. nova and Saniculo-Abietum equi-trojani ass. nova are new to the plant science.